El género Obrium Dejean, 1821 (Coleoptera, Cerambycidae, Obriini) en Venezuela - Joly, Luis J. (Papéis Avulsos de Zoologia, 2010)
Four new species of Obrium are described from Venezuela: Obrium asperatum sp. nov., O. clavijoi sp. nov., O. latecinctum sp. nov. and O. semiduffusum sp. nov. A key to South American species is presented.